Improving Coal Loading and Unloading Performance at Loading and Unloading Terminals with Lean Thinking Concept - Ridho, Alvin Ichwannur; Siswanto, Nurhadi (Journal Research of Social Science, Economics, and Management, 2025)
The coal mining logistics industry in Indonesia has a strategic role as the world's largest coal producer, with a significant contribution to state revenue. This study aims to analyze the main obstacles, wastes that occur, and proposed improvements in the coal loading and unloading process at PT XYZ to increase efficiency and productivity through a lean thinking approach. The methodology of this research includes a qualitative approach through value stream mapping and quantitative using fishbone diagrams to produce a comprehensive analysis. The analysis is carried out through process activity mapping, the preparation of current state maps, and the design of future state maps to provide suggestions for improvement. Based on the results of the study, several recommendations for improvement were obtained from the results of the analysis on coal unloading or loading activities which included Value Added (VA) or Necessary but Non-Value Added (NNVA). The proposed improvements include the application of double crossing dismantling methods, digitization of administrative processes, and the use of drone technology to facilitate the physical inspection process in the field. If the proposal can be implemented, there will be an increase in the time effectiveness of coal loading and unloading activities by 14.20%, with details of unloading activities increasing by 25.30% or from 1,004 minutes to 750 minutes, and coal loading activities by 3.10% or from 3,067 minutes to 2,972 minutes.